Effects of oceanic circulation and volcanic ash-fall on calcite dissolution in bathyal sediments from the SW Pacific Ocean over the last 550ka - COBIANCHI, MIRIAM; MANCIN, NICOLETTA; LUPI, CLAUDIA; Bordiga, M.; Bostock, H. C. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2015)
The effects on calcite dissolution of both oceanic circulation and volcanic ash-fall were evaluated in lower bathyal sediments over the last 550 ka record fromcoreMD97-2114, recovered on the northern slope (depth of 1936 m, in the Pacific DeepWater, PDW) of the Chatham Rise (east of New Zealand, SWPacific Ocean). This area has been impacted by changes in glacial/interglacial circulation and ocean chemistry as well as by the explosive volcanic activity of the Taupo Volcanic Zone. Severalmicro-paleontological dissolution proxies, based on planktonic foraminifera and calcareous nannofossils, were analysed in order to evaluate the calcite dissolution of the deep-sea sediments. These were compared with a couple of proxies of primary productivity (benthic foraminiferal epifaunal/ infaunal ratio and δ13Cbenthic foraminifera) and the abundance of volcanic glass. The dissolution proxy data from MD 97-2114 were compared with two nearby ODP sites, ODP 1123 (3290 m deep, bathed by the lower Circumpolar Deep Water, LCDW) and ODP 1125 (1365 m deep, bathed by the Antarctic IntermediateWater, AAIW). The results suggest: (1) the calcite dissolution/preservation cycles at all three core sites showGlacial–Interglacial (G–I) periodicities that match the previously described “Pacific-style” CaCO3 cycles; (2) several short-termdissolution events do not followthis general scheme and occur following tephra deposition. The dissolution related to the tephra deposition seems to have mostly affected calcareous nannofossils, thus we hypothesise that the ashfall induced a temporary reduction of the surfacewater pH (below7.8),which affected the coccolithophores that inhabit the surface waters. (3) Other short-term dissolution events (1000 years) are unrelated to tephra deposition and are possibly driven by the slowing of deep-sea circulation and a reduced Deep Western Boundary Current (DWBC). This lead to the dominance of older, more corrosive Pacific Deep Water (PDW) flowing in to the region, resulting in coeval dissolution episodes at all ...